RUMAH TERAPI BAGI REMAJA PENDERITA TRAUMA INNER CHILD - Tanoto, Reynaldi; Lianto, Fermanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
The Inner Child within a person is a past and present experience that can occur whenever and wherever the individual is. An experience can significantly impact behaviour when the child enters adulthood, even in old age. For this reason, it is necessary to study more deeply the cause and effect of the Inner Child with a descriptive analysis method and a narrative architecture approach that can help find solutions to recover Inner Child trauma. Based on the data, Inner Child is mostly experienced by teenagers, namely in cases of Domestic Violence. Parents as perpetrators cannot provide good parenting to children, so when children reach adulthood, their behaviour and emotions become unstable. A high awareness and empathy must be needed to restore these adolescents’ psychic and mental health. One of the design strategies applied is social care, where a camp-like lodging place (glamping) is provided to provide a sense of togetherness and kinship. Then, it is also necessary to use several therapeutic techniques from psychologists to restore the Inner Child trauma of adolescents. The therapeutic techniques performed would be converted into the form of architectural space as an act of empathy for adolescent victims of domestic violence who have poor Inner Child trauma. The space plays with materials, textures, nuances, and light as a procedure for Inner Child therapy techniques to release the inner child trauma. Keywords:  adolescent victim; inner child; narrative architecture; therapeutic home; trauma Abstrak Inner Child yang berada di dalam diri seseorang merupakan pengalaman masa lalu dan masa yang sekarang dapat terjadi kapanpun dan dimanapun individu berada. Suatu pengalaman yang dialami dapat berdampak besar kepada perilaku ketika anak tersebut telah masuk usia dewasa, bahkan usia tua. Untuk itu perlu dikaji lebih dalam mengenai sebab akibat Inner Child dengan metode deskriptif analisis dan pendekatan arsitektur naratif yang dapat membantu menemukan solusi untuk memulihkan trauma Inner Child. Berdasarkan data Inner Child banyak dialami oleh remaja yaitu pada kasus Kekerasan Dalam Rumah Tangga (KDRT). Orang tua sebagai pelaku tidak dapat memberikan pola asuh yang baik kepada anak, sehingga ketika anak menyentuh usia dewasa, tingkah laku serta emosi mereka menjadi tidak stabil. Perlu adanya tingkat awareness serta empati yang tinggi untuk memulihkan psikis serta mental remaja tersebut. Strategi desain yang diterapkan salah satunya yaitu social care, dimana disediakan tempat penginapan yang menyerupai perkemahan (glamping) untuk memberikan makna kebersamaan dan kekeluargaan. Lalu perlu juga menggunakan beberapa teknik terapi dari ahli psikolog untuk memulihkan trauma Inner Child remaja. Teknik terapi yang dilakukan akan dikonversikan ke dalam bentuk ruang arsitektur sebagai tindakan empati kepada remaja korban KDRT yang memiliki trauma Inner Child yang buruk. Ruang bermain dalam material, tekstur, nuansa, dan cahaya sebagai prosedur teknik terapi Inner Child untuk melepaskan emosi.